Institutional Capacity and the Local Governance Gap: Explaining the Limited Effectiveness of Affirmative Policies in Papua - Abdullah, Muh Tang; Syaputra, Much Faisal; Emynorane, Ralaivao Hanginiaina (Publisia: Jurnal Ilmu Administrasi Publik, 2026)
This study examines the role of institutional capacity in shaping the effectiveness of affirmative policy implementation within the local governance context of Southwest Papua. Using a qualitative case study approach, data were collected through interviews, document analysis, and institutional reports. The findings reveal that, despite strong normative recognition of Indigenous Papuans (OAP), affirmative policies remain largely symbolic and have not produced substantial structural changes. This condition is driven by the misalignment between institutional design, institutional capacity, and governance structure. The study offers a theoretical contribution by proposing the Local Governance Gap Model (LGGM), which explains how the interaction of these dimensions constrains policy effectiveness in decentralized and asymmetric governance contexts. In addition, this research introduces a distinction between symbolic and substantive policy outcomes as a critical analytical lens. This study extends institutional capacity theory by positioning capacity as structurally embedded rather than purely organizational. Unlike previous studies that focus on institutional roles or policy implementation in isolation, this research integrates institutional capacity, affirmative policy, and governance structure into a unified analytical framework. The findings highlight that effective affirmative governance requires alignment between authority, capacity, and governance context to move beyond symbolic recognition toward substantive outcomes.